Green Open Spaces and Sustainable Settlements from the Islamic Perspectives – Case Study Kampung Kauman - Junara, Nunik; Triyadi, Sugeng (International Journal of Engineering and Technology, 2026)
Sustainable settlement in Islamic perspectives can be defined as a multi-dimensional process that seeks to achieve a balance between economic and socio-cultural aspects, and also the environmental aspect. There are many quotes of verses in the Quran and Hadith that leads to the belief that Islam as a Rahmatan lil Alaamiin, where men are encouraged to act wisely in treating nature and all living things in it. One aspect of the natural environment that closed to human is plants. In the settlement, the availability of green open space is highly recommended.  The availability of green open space in the neighborhood, both the public and private green open spaces is expected to reduce the effects of global warming that has engulfed various parts of the world. Green open space that can be viewed from the angle of eco-aesthetic and eco-medical in sustainable architecture, is expected to increase the temperature and provide aesthetic impression to the surrounding environment.This paper attempts to discuss the principles of Islamic values related to the green open space. This paper also aims to raise awareness of the importance of the theme of sustainability in settlements, especially in big cities. Analysis of the availability of green open space in Kauman Malang is one example of the effort to apply the principles of sustainable settlement.
Keywords: Green Open Space; Sustainable Settlements; Islamic Values. Kampung Kauman Malang